ANALISIS KADAR PROTEIN PADA ACOROIDES MILK BERDASARKAN SUHU DAN LAMA PENYIMPANAN - Meviona Muskitta; Prelly M Tuapattinaya (BIOPENDIX, 2016)
Background: Economically privilege Enhalus acoroides seed can be used as a food ingredient because it has a complete nutrional content and relatively high. The nature of these nutrients easily digested and absorbed, so it can be processed to be used as milk. Method: To determine levels of protein in milk acoroides based on a temperature of 200C and 450C for storage of 0, 6, and 12 hours using kjedhal. Result: Based on test result using methods kjedhal protein, it is known that the longer the stage in high temperatures, it can increase the protein content. Conclusion: The highest increase in protein occurs at a temperature of 450C for 12 hours with a storage protein levels by an average of 1.9473% and the lowest increased protein 200C lows temperature during storage 0 hours with an average protein content of 1.5071%